Royall Tyler in Hungary: An American of the League of Nations and Hungarian Reconstruction Efforts, 1924–1938 - Peterecz, Zoltán (Hungarian Journal of English and American Studies, 2021)
American-Hungarian relations were rarely closer on the personal level than in the interwar years. Although the United States followed the path of political and diplomatic isolation from Europe in the 1920s and 1930s, and its absence in the League of Nations was conspicuous, in the financial and economic realm it remained more active, and many Americans worked in the various reconstruction projects across Europe either in their private capacities or under the auspices of the League. Royall Tyler was one such person who spent the larger part of the 1920s and 1930s in Hungary. Since the start of the financial reconstruction of Hungary in 1924, Tyler was a constant participant in Hungarian financial life, a contact between the Hungarian government and the League of Nations, and a sharp observer of events throughout the years he spent in Hungary and Europe. This essay focuses on his activities concerning Hungary’s financial and economic reconstruction and recovery. (ZP)